Right atrium to pulmonary capillary wedge pressure ratio is associated with right ventricular failure and mortality after left ventricular assist device surgery. (25th November 2020) - Segev, A; Nathanzon, S; Fardman, A; Morgan, A; Lavee, J; Grupper, A
Abstract: Introduction: Right ventricular failure (RVF) is a major cause of morbidity and mortality after left ventricular assist device (LVAD) implantation. We investigated the role of right atrium to pulmonary capillary wedge pressure (RA/PCWP) ratio as a preoperative predictor of postoperative RVF after LVAD surgery. Methods: A retrospective analysis of all consecutive patients who received continuous-flow LVADs (HeartMate 2, 3, and HVAD) between August 2012 and May 2018 in a single tertiary center. INTERMACS profile 1 patients were excluded. RA/PCWP ratio was calculated for the entire cohort and divided into quartiles (Q). Patients were stratified into high (Q4) vs. low (Q1–3) RA/PCWP ratio. The primary end point was the composite of in hospital mortality and RVF (defined as the need for a right ventricular assist device or inotrope dependence for >7 days). The secondary endpoint was readmission within 14 days after discharge. Results: The study cohort consisted of 59 patients (15 patients in the high RA/PCWP group and 44 patients in the low RA/PCWP group) with a median follow-up of 21 months (Interquartile range 14–31). The mean age was 56±11 years and the majority of patients were male (88%). Patients were classified as INTERMACS profile 2 (34%), 3 (19%) or 4 (47%). Preoperative clinical, laboratory, and echocardiographic parameters were similar in both groups except for a larger proportion of patients with a dilated right ventricle and above moderate tricuspid regurgitation in the high compared to the low RA/PCWP group (73% vs. 29%; P=0.006 and 40% vs. 2%; P=0.001, respectively). Overall, 7 patients (12%) developed the primary end-point and 9 patients (15%) developed the secondary end-point. Univariate analysis demonstrated that high RA/PCWP is associated with both primary and secondary end-points (odds ratio [OR], 7.6; 95% confidence interval [CI] 1.2–47.2, P=0.029 and OR, 6.25; 95% CI 1.3–28.5, P=0.018, respectively). On multivariable analysis, the association remained significant after adjustment for INTERMACS score (OR, 10.6; 95% CI 1.4–80.9, P=0.022 and OR, 7.9; 95% CI 1.5–42.2, P=0.015, respectively). Using receiver operating characteristic curve (ROC) derived cut-points, RA/PCWP >0.57 provided 67% sensitivity and 79% specificity (C-statistic = 0.73) for the prediction of in hospital mortality and RVF and 56% sensitivity and 84% specificity (C-statistic = 0.69) for the prediction of readmissions within 14 days after discharge. In comparison, in our cohort using ROC-derived cut points, pulmonary artery pulsatility index, an established RVF predictor, of less than 1.84 provided 40% sensitivity and 20% specificity (C-statistic = 0.3) for the prediction of inhospital death and RVF. Conclusion: RA/PCWP ratio may help to identify patients at high risk of developing adverse clinical outcomes, including RVF and mortality, after LVAD surgery. Funding Acknowledgement: Type of funding source: None